Analyzing Moisture at the Drying Process of Spice Plants - Djurayev Kh.F.; Mizomov M.S. (Zien Journals, 2022)
This article illustrates those recent developments in the production of high dried spices and herbs. Thermal and physical properties of the materials under study light-reflecting infrared drying in vacuum taking into account using the device of artichoke ends and spices and herbs developed efficient processing technology. Infrared extend electromagnetic field to the item being dried the development prepare is quickened by 4-5% due to the utilize of vibration recognized. Given negligible misfortune of inulin substance, convective within the drying strategy up to 33.3 mg% and by neighborhood producers up to 8-9 mg% within the strategy utilized, up to 45.4 mg% within the proposed strategy the sum of inulin substance stored. The sum of ascorbic corrosive remaining within the dried zest plant up to 0.77 mg% within the proposed strategy, 0.15 mg% within the hellion drying strategy up to 0.71 mg% within the drying strategy, within the convective drying strategy. Up to 0.12 mg% and within the way utilized by nearby producers Put away up to 0.59 mg% and endeavors to detail the relative merits of chosen as of late created drying procedures with center. Outlook for future research trends and challenges for dehydration of spices and herbs is also discussed.
Keywords: Product quality; process quality; nutritional value; amount of essential oils/aroma